Shari’ah Compliance Rights in Implementation of Legal Principles on Shari’ah Banking - Ariadin Ariadin; Syamsuddin Pasamai; Abdul Agis; Abdul Qahar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to find out, analyze and discover the nature of sharia compliance in Sharia banking business activities. This type of research is empirical normative with non-doctrinal or sociological approaches. Researchers used qualitative analysis of the results of the questionnaire and interviews as well as primary, secondary and tertiary legal materials. The results showed that; The essence of Shariah Compliance in Sharia Banking is for the purpose of benefit, prosperity and happiness, blessing, and worship to reach falah (glory). Research suggestions are the need for more intensive socialization, education and awareness process to the public / customers in order to understand the existence and function of sharia banking, 2) The need for aspects of sharia compliance for sharia banking to be a basic value, principles and guidelines, both stakeholders, officials, employees / employee, Sharia Supervisory Board.